EFFECT OF WORK ENVIRONMENT, LEADERSHIP, COMPENSATION AND WORK TRAINING ON EMPLOYEE ENGAGEMENTS IN STAR HOTELS IN BATAM - Antony Sentoso (Journal of Business Studies and Management Review, 2020)
The purpose of this study is to analyze the factors that affect employee retention. Factors that affect employee retention are SHRM Practices which include Recruitment & Selection, Training & Career Development, Performance Appraisal and Compensation & Benefits. There are also other factors, namely Demographic & Professional Characteristics. This research uses purposive sampling method and the data is processed using PLS. The number of respondents in this study was 259 out of 270 questionnaires distributed. Respondents of this study were employees of 4 star hotels in Batam which had satisfactory scores on the travel site, Traveloka, above 8.6. Based on the results of the research conducted and the data that have been processed, the SHRM practices variable has a significant effect on the employee retention variable. Where in terms of recruitment, training, compensation and benefits have a positive influence on employee retention.